2023
DOI: 10.1002/oby.23948
|View full text |Cite
|
Sign up to set email alerts
|

A newly identified compound activating UCP1 inhibits obesity and its related metabolic disorders

Ken Onodera,
Yutaka Hasegawa,
Nozomi Yokota
et al.

Abstract: ObjectivePromoting thermogenesis in adipose tissue has been a promising strategy against obesity and related metabolic complications. We aimed to identify compounds that promote thermogenesis in adipocytes and to elucidate their functions and roles in metabolism.MethodsTo identify compounds that directly promote thermogenesis from a structurally diverse set of 4800 compounds, we utilized a cell‐based platform for high‐throughput screening that induces uncoupling protein 1 (Ucp1) expression in adipocytes.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…A recent study identified Kcnc2 as a thermogenic gene in adipocytes. The PKA‐p38 MAPK‐KCNC2‐UCP1 signaling pathway is a potential target for obesity treatment 53 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study identified Kcnc2 as a thermogenic gene in adipocytes. The PKA‐p38 MAPK‐KCNC2‐UCP1 signaling pathway is a potential target for obesity treatment 53 …”
Section: Discussionmentioning
confidence: 99%
“…The PKA-p38 MAPK-KCNC2-UCP1 signaling pathway is a potential target for obesity treatment. 53 The expression and potential function of Kcnc2 in hypothalamus…”
Section: Hub Genes For Metabolic Disorders In Offspring Due To Matern...mentioning
confidence: 99%